Laws on Economic Security: An Analytical Study of Some Ancient Indian Law Books - Harekrushna Mishra; Gunadhara Bhandary (Budapest International Research and Critics University, 2022)
The king or the master of a Nation did not want to see any kind of misery for his subjects. It may be thought that if people are in a problem then they will go to the king as if a son goes to the father for the solutions. Then the king will be the part of the problem and he has to pay attention to it. But if there is less or no problem in his state then the king also can think about the prosperity of the state. This can be experienced in the history of medieval India. There was continuous fighting between the Indian Kings as well as the wars between Islamic invaders and indigenous Hindu Kings. During this period almost all kings deviated from the developmental agenda and as a result, the common man, as well as the weaker section, became weaker and India became economically backward. This paper intends to through a fresh light on the so called dark side of the Hindu social system.